KEKUATAN MENGIKAT KONTRAK BAKU DALAM TRANSAKSI ELEKTRONIK - Frisca Indiradewi, Pande Putu; Puspawati, I Gusti Ayu; Rudy, I Dewa Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013, 2013)
Goals in research papers titled Raw Power Binding Contract Electronic Transactions is to know the power of raw covenant through electronic media. The method used is the method of normative legal research, the approach through the perspective of the norms that have been there, or in other words a form of inventory research legislation in force, trying to find the basic principles or philosophy of law , or research in the form of legal discovery efforts are in accordance with a particular case.The results obtained from these problems is an open legal system and in the act. No. 11 year 2008 about Information and Electronic Commerce (UU ITE) and in the act. No. 8 year 1999 about Consumer Protection (UUPK) has provided the legal basis for give the position of both parties in the same position on the powerful raw deal in electronic transactions. So that these agreements have the same legal force as treaties are binding konsvensional.
Keywords: Binding strength, Standard Contract, Consumer, Electronic Transactions